(3cfg eG dGHO ddeQjO efgs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3GHh HcQ Hf GSMGb Hf GHQGgje GdRGgOi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf SCdJ CjgG GdeQjO GdeSJQTO Yf cfg eG dGHO dc efg aCLHJc ai gPg GdChQGb Ydi eG SCdJ EYde CjgG GdeQjO Cf GdbQH ef Gddg dGjYde EdG HJYQjag s
(3BNQgG (B:s
(3hbGd ai WdH GdMdGd (B( (3jQjOhf YQV GdOfjG hGddg jQjO GdBNQI (B) ( (3hGMSfhG Ef Gddg jMH GdeMSfjf (B) (3GfJgi eG dGHO ddeQjO efg hgh cJGH cfg GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf NW GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
Keywords: (3GdJUha hGdBOGH GdTQYjIs